Pengaruh Pajak, Tunneling Incentive, Dan Good Corporate Governance Terhadap Transfer Pricing - Indra Wijaya; Anisa Amalia (Fakultas Ekonomi Dan Bisnis, Universitas Mercu Buana, Jakarta, 2020)
This research aimed of the study was to determine the effect of tax, tunneling incentive and good corporate governance (GCG) on transfer pricing. Transfer pricing was measured using related party transaction (RPT). Manufacturing companies at the Indonesian Stock Exchange (IDX) period 2013-2017 were used as research totaling 25 companies, and the samples was taken by purposive sampling method. The analysis technique used was a binary logistic regression. This result of this research showed that tax measured using effective tax rate (ETR) had positive effect on transfer pricing, and good corporate governance measured using a general audit committe had negative effect on transfer pricing, while tunneling incentive measured using ownership of foreign share capital more than 20% had no effect on transfer pricing.